Dissemination of novel Tn7 family transposons carrying genes for synthesis and uptake of fimsbactin siderophores among Acinetobacter baumannii isolates. Issue 3 (22nd March 2021) - Hamidian, Mohammad; Hall, Ruth M.
Abstract : Acinetobacter baumannii is a successful opportunistic pathogen that can compete for iron under iron-limiting conditions. Here, large novel transposons that carry genes for synthesis and transport of the fimsbactin siderophores present in some A. baumannii strains were examined. Tn 6171, originally found in the A. baumannii global clone 1 (GC1) lineage 2 isolate D36, includes tns genes encoding proteins related to the TnsA, TnsB, TnsC transposition proteins (50–59 % identity), TnsD targeting protein (43 % identity) and TnsE (31 % identity) of Tn 7, and is found in the chromosome downstream of the glmS gene, the preferred location for Tn 7, flanked by a 5 bp target site duplication. Tn 6171 is bounded by 29 bp inverted repeats and, like Tn 7, includes additional TnsB binding sites at each end. Tn 6171 or minor variants were detected in the equivalent location in complete or draft genomes of several further A. baumannii isolates belonging to GC1 [sequence type (ST) 1, ST81, ST94, ST328, ST623, ST717], GC2 (ST2) and ST10. However, in some of these isolates the surrounding glmS region was clearly derived from a different A. baumannii lineage, indicating that the transposon may have been acquired by replacement of a segment of the chromosome. A recombination-free phylogeny revealed that there were several transposon acquisition events in GC1. The GC1 isolates were mainly lineage 2, but a potential third lineage was also detected. A related transposon, designated Tn 6552, was detected in ATCC 17978 (ST437) and other ST437 isolates. However, the Tn 6552 tnsD targeting gene was interrupted by an ISAba12, and Tn 6552 is not downstream of glmS .